2000
DOI: 10.1046/j.1469-0705.2000.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

The pulmonary vein Doppler flow velocity waveform: feature analysis by comparison of in vivo pressures and flows with those in a computerized fetal physiological model

Abstract: Flow reversal in pulmonary veins during atrial contraction indicates hypoxia, but change of shape of the FVW envelope reflects the changes in the pressure waveform of the left atrium. Of the major veins the pulmonary vein Doppler FVW gave the truest representation of atrial pressure response to both intracardiac and systemic vascular status. Although current indices indicate general fetal condition, more specific indices are needed if pulmonary venous flow is to be used as an end-point. A pulmonary vein pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Other factors involved have been evaluated, such as left atrium relaxation and compliance and left ventricular function. [21][22][23][24][25][26][27] Pulmonary vein relaxation, mediated by C-type natriuretic peptide, is uniform and thus does not allow segmental variations. 28 The effects of vessel tapering in the pulmonary circulation have been studied by nonlinear models, 6,10 and the role of the vessel cross-sectional area in the flow wave dynamics has also been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors involved have been evaluated, such as left atrium relaxation and compliance and left ventricular function. [21][22][23][24][25][26][27] Pulmonary vein relaxation, mediated by C-type natriuretic peptide, is uniform and thus does not allow segmental variations. 28 The effects of vessel tapering in the pulmonary circulation have been studied by nonlinear models, 6,10 and the role of the vessel cross-sectional area in the flow wave dynamics has also been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of pulmonary venous flow velocity, may be altered in many physiologic and pathologic situations, such as heart rate 24 , cardiac output 25 , absolute pulmonary flow 26 , left atrial pressure 22 and function, mitral valve function, left ventricle pressure and function 22 . Talbert and Johnson 27 suggested that the change of shape of the pulmonary venous flow waveform reflects the changes in the pressure waveform of the left atrium and represent the atrial pressure response to both intracardiac and systemic vascular status.…”
Section: Discussionmentioning
confidence: 99%
“…The present study uses this technique to establish gestational age‐specific reference ranges for blood flow velocities and impedance indices in the fetal pulmonary vein. Pulmonary vein Doppler spectra are predominantly modulated by the changes in left atrial pressure during the cardiac cycle . The pattern of pulmonary venous flow indicates a dependence on fetal heart rate, cardiac output, absolute pulmonary blood flow, left atrial pressure and mitral valve function.…”
Section: Discussionmentioning
confidence: 98%